Physiological responses of cacharas Pseudoplatystoma reticulatum submitted to natural anesthetics - Sanchez, Milena Souza dos Santos; Rodrigues, Robson Andrade; Nunes, André Luiz; Oliveira, Aline Mayra da Silva; Fantini, Letícia Emiliani; Campos, Cristiane Meldau de (Semina: Ciências Agrárias, 2014)
The present study the aimed to evaluate the induction time, recovery time and physiological responses of cacharas, Pseudoplatystoma reticulatum, submitted to eugenol and menthol. 42 cacharas were exposed to eugenol 100 mgL-1 (n=14) and menthol 150 mgL-1 (n=14) and the control group (n=14) which were not exposed to any anesthetics. At the time 0 and 24 hours after induction, the bloods of 7 fishes per treatment were collected to measure the hematologic parameters and plasma glucose evaluation. The recovery was conducted in aquariums free of anesthetic, and induction and recovery times were monitored. The results were submitted to analysis of variance (P<0.05) and the means were compared by Tukey test (P<0.05). Both anesthetics, in respective concentrations, induced fishes to surgical anesthesia. There was no significant difference (P>0.05) for induction time, however the recovery time had a significant reduction (P<0.05) for the menthol 150 mgL-1. There was no treatment effects on hematologic parameters, except for mean corpuscular volume (VCM), which was observed an interaction effect between factors, once fish anesthetized with eugenol showed significant reduction (P<0.05) on VCM 24 hours after anesthesia. Plasma glucose values did not differ at 0 hour after induction. 24 hours after induction, both control group and fishes exposed to eugenol and menthol were significantly reduce in VCM. Eugenol at 100 mgL-1 and menthol at 150 mgL-1 may be safely induced in cachara during biometrics procedures.